Fekete-Szegö Problem for $α$-Quasi Convex Functions of Order $β$ (Journal of Informatics and Mathematical Sciences, 2012)
For $f \in Q_{α,β}^c$, sharp bounds are obtained for the Fekete-Szegö functional $|a_3 - μ a_2^2|$, where $μ$ is real.
Keywords: Analytic function; Univalent convex function; $α$-quasi-convex function of order $β$; Fekete-Szegö functional